Gain-clamping techniques in two-stage double-pass L-band EDFA - Harun, S. W.; Samsuri, N. Md.; Ahmad, H. (2006)
Two designs of long-wavelength band erbium-doped fiber amplifier (L-band EDFA) for gain clamping in double-pass systems are demonstrated and compared. The first design is based on ring laser technique where a backward amplified spontaneous emission (ASE) from the second stage is routed into the feedback loop to create an oscillating laser for gain clamping. The gain is clamped at 18.6 dB from -40 to -8 dBm with a gain variation of less than 0.1 dB and a noise figure of less than 6 dB. Another scheme is based on partial reflection of ASE into the EDFA, which is demonstrated using a narrowband fiber Bragg grating. This scheme achieves a good gain clamping characteristic up to -12 dBm of input signal power with a gain variation of less than 0.3 dB from a clamped gain of 22 dB. The noise figure of a 1580 nm signal is maintained below 5 dB in this amplifier since this scheme is not based on lasing mechanism. The latter scheme is also expected to be free from the relaxation oscillation problem.